APLIKASI KALKULATOR KOMPONEN ELEKTRONIKA BERBASIS ANDROID - Setiawan, Ade (STKIP PGRI Sumatera Barat, 2021)
Android is the most popular OS today, many of which use android as a learning medium, knowledge and tools for calculating examples such as making electronic component calculators that can help repair technicians of electronic devices. In this study, the authors made an electronic component calculator application that can calculate a component value by reading the component codes carried out by the application. In making this application using Android Studio tools to create the source code. Adobe Photoshop is of course for the design. Of course, this is in line with the purpose of the author's research. The results of research by electronic device repair technicians and students are greatly helped by this application.